Analisis Pendalilan Sifat Waḥdāniyyah Allah Menurut Ibn Juzay: Kajian Terhadap Kitab Al-Nūr Al-Mubīn Fi Qawā‘Id ‘Aqā’id Al-Dīn: Analysis of the Prooffing for Waḥdāniyyah of Allah According to Ibn Juzay: A Study of the Book al-Nūr al-Mubīn fi Qawāʿid ʿAqāʾid al-Dīn - Mohd Khalil, Ahmad Faiz; Hamat, Mohd Fauzi; Zainal Abidin, Azmil (Al-Basirah Journal, 2025)
The discourse on the attribute of waḥdāniyyah (oneness) of Allah is a central theme in the discipline of Ilm al-Kalam, which is often referred to as the science of Tawḥīd. Scholars have presented various arguments to affirm Allah’s oneness comprehensively and accurately. This study focuses on the reasoning found in al-Nūr al-Mubīn, authored by Muhammad Ibn Juzay al-Gharnāṭī, emphasizing rational arguments derived from the Quran. The study employs a qualitative research approach by analyzing the book’s textual content. Findings reveal that Ibn Juzay systematically arranged Quranic evidence for waḥdāniyyah using rational and logical frameworks. This affirms that rational methods in the Ash’ari school of ‘Ilm al-Kalam are rooted in the Quran rather than external influences like Greek philosophy. The study contributes to understanding the art of rational argumentation in the Quran, demonstrating its decisive (qatʿi) and accessible nature, suitable for diverse societal contexts.